2009
DOI: 10.1682/jrrd.2008.12.0163
|View full text |Cite
|
Sign up to set email alerts
|

Influence of neurological level of injury in bones, muscles, and fat in paraplegia

Abstract: Abstract-To investigate the influence of the neurological level of injury in bone mineral content (BMC) and mechanical properties, lean mass (LM), and fat mass (FM) among paraplegics with a similar duration of paralysis (DOP), we separated 30 paraplegics into group A (15 men, high-level paraplegia) and group B (15 men, low-level paraplegia) and compared them with group C (33 men, nondisabled). In all subjects, we measured stress-strain index (SSI) at 14% (SSI 2 ) and 38% (SSI 3 ) of the tibia length and the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 20 publications
1
15
0
3
Order By: Relevance
“…the extent of impairment of motor and sensory function is important, because tetraplegics are more likely to lose more bone mass throughout the skeleton than paraplegics (Tsuzuku et al, 1999). In paraplegics legs' BMC was reduced vs. controls, independently of the neurological level of injury and negatively correlated with the duration of paralysis in total paraplegic group, but after investigation according to the neurological level of injury this correlation was due to the strong correlation of high paraplegics' legs BMC with the duration of paralysis, meaning that the neurological level of injury determines the extent of bone loss (Dionyssiotis et al, 2009). The similar severity of demineralization in the sublesional area was shown between paraplegics and tetraplegics, and the extent of the bone loss may be variable (Demirel et al, 1998;Tsuzuku et al, 1999;Dauty et al, 2000).…”
Section: Spinal Cord Injurymentioning
confidence: 86%
“…the extent of impairment of motor and sensory function is important, because tetraplegics are more likely to lose more bone mass throughout the skeleton than paraplegics (Tsuzuku et al, 1999). In paraplegics legs' BMC was reduced vs. controls, independently of the neurological level of injury and negatively correlated with the duration of paralysis in total paraplegic group, but after investigation according to the neurological level of injury this correlation was due to the strong correlation of high paraplegics' legs BMC with the duration of paralysis, meaning that the neurological level of injury determines the extent of bone loss (Dionyssiotis et al, 2009). The similar severity of demineralization in the sublesional area was shown between paraplegics and tetraplegics, and the extent of the bone loss may be variable (Demirel et al, 1998;Tsuzuku et al, 1999;Dauty et al, 2000).…”
Section: Spinal Cord Injurymentioning
confidence: 86%
“…Another factor that may have contributed are the different deficiencies of subjects of each functional class group, as it is the case of low and intermediate groups, which are mostly composed of individuals with SCI and Poliomyelitis, and tend to present increased motor impairment and increased body fat mainly in paralyzed limbs [18][19][20] . Regarding body composition profile, it was observed that women presented significantly higher body mass index than men, which is in agreement with Guedes and Guedes 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord injury paraplegic men were allocated into 2 subgroups based on the neurological level of injury; subgroup A (n=16, Thoracic (T)4-T7 neurological level of injury) and subgroup B (n=15, T8-T12 neurological level of injury). BMDtrab: BMD trabecular; BMDcort: BMD cortical; (adapted from Dionyssiotis et al, 2011a, with permission).…”
Section: Duration Of Paralysis and Bone Steady Statementioning
confidence: 99%
“…In addition, muscle spasms affecting the lower leg would mainly be extension spasms resulting in plantar flexion thus creating little resistance to the contracting muscles. Furthermore, the measuring sites of the tibia did not include any muscle insertions of either the knee or the ankle extensor muscles (Dionyssiotis et al, 2011a;Dionyssiotis, 2011c). Other investigators also have not been able to establish a correlation between BMD and muscle spasticity (Lofvenmark et al, 2009).…”
Section: Spasticitymentioning
confidence: 99%